Evaluation of Physics Practicum for High School and MA Students in South Kalimantan at the Epic Olympiad at the Integrated Laboratory of UIN Antasari Banjarmasin - Sitti Rahmasari; Fitri Nur Hikmah (Journal of Social Research, 2026)
This study examines the evaluation of physics practicum activities conducted by senior high school and Madrasah Aliyah (MA) students from South Kalimantan during the EPIC Olympiad at the Integrated Laboratory of UIN Antasari Banjarmasin. The background of this research is based on the importance of laboratory-based learning in improving students’ scientific literacy, experimental skills, and understanding of physics concepts in the era of 21st-century education. However, differences in students’ abilities in operating laboratory equipment, following procedures, analyzing data, and preparing practicum reports indicate the need for a comprehensive evaluation of practicum implementation. This study aims to evaluate students’ practicum performance and practicum report quality during the EPIC Olympiad. The research employed a descriptive qualitative approach involving senior high school and Madrasah Aliyah students participating in the Olympiad. Data were collected through observation sheets used for assessing practicum performance and questionnaires used for evaluating practicum reports. The collected data were analyzed using percentage-based descriptive analysis. The results showed that students’ practicum performance achieved an average score of 78%, categorized as good, particularly in teamwork and practicum participation. Meanwhile, the practicum report evaluation obtained an average score of 67.6%, categorized as fairly good, with weaknesses identified in data analysis, discussion, and conclusion writing. In conclusion, the EPIC Olympiad contributes positively to strengthening students’ scientific competence, although further improvement is still needed in technical laboratory skills and scientific reporting abilities.